Development of Ethno-Virtual Reality Media in Biotechnology Project Learning to Realize Collaborative and Creative Skills - Umami, Hanifatul; Sudarmin, Sudarmin; Wiyanto, Wiyanto; Fibriana, Fidia; Annisa, Uma (Universitas Negeri Semarang, 2025)
The development of Ethno-Virtual Reality (Ethno-VR) media in biotechnology project learning aims to analyze its development process, characteristics, validity, and practicality. This study uses a Research and Development (R&D) approach with the ADDIE model, covering five stages: Analysis, Design, Development, Implementation, and Evaluation. However, the implementation stage has not yet been carried out. The research subjects were Class X-4 students at SMA Negeri 1 Randudongkal. Data collection techniques included interviews, characteristic and validation questionnaires, and teacher and student response questionnaires. The findings show that Ethno-VR media received an excellent rating of 92.10% for its content and cultural feasibility, integration with ethnoscience, alignment with project-based learning, and potential to foster collaborative and creative skills. The media was deemed highly valid, with material validation scores of 96.66% and media validation scores of 94.60%. Its practicality was also rated very high, with teacher response scores at 93.75% and student responses at 86.48%. In conclusion, the developed Ethno-VR media demonstrates excellent characteristics, high validity, and strong practicality, making it highly suitable for implementation in high school biotechnology project learning.